2020
DOI: 10.3390/ijerph17030955
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparity between the Older Rural-to-Urban Migrant Workers and Their Rural Counterparts in China

Abstract: Background: China’s older rural-to-urban migrant workers (age 50 and above) are growing old, but comparative health research on older rural-to-urban migrants in China is still in its infancy. The aim is to explore the health status of older rural-to-urban migrant workers in China; as well as to identify health disparity between older rural-to-urban migrant workers and older rural dwellers. Methods: This study employed self-assessed health status (SAH) and chronic disease condition to explore the health status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Numerous variables are available in CHARLS. Followed by prior empirical investigations [9,[23][24][25][26], all possible variables that may produce SAH of the elderly were considered in our study. The definition and measurement of variables in this study were all shown in Table 1.…”
Section: Description Of Variablesmentioning
confidence: 99%
“…Numerous variables are available in CHARLS. Followed by prior empirical investigations [9,[23][24][25][26], all possible variables that may produce SAH of the elderly were considered in our study. The definition and measurement of variables in this study were all shown in Table 1.…”
Section: Description Of Variablesmentioning
confidence: 99%
“…Migration for work is not randomly assigned and there is "self-selection based upon personal circumstances" [22], a crude comparison of the health services utilization using only logistic regression may ignore the confounding factors. Our study tackled a methodological issue in assessing the "causal effect" on the change in status by CEM, because older rural-tourban migrant workers and rural counterparts can become (or very close to) identical in relation to individual characteristics after CEM [2,23]. In our study, the employment status (be employed outside the country for 6 months or more in the past year) is matched.…”
Section: Coarsened Exact Matchingmentioning
confidence: 99%
“…As far, rural-to-urban migrant workers have made great contributions to the development of urbanization and industrialization in China. Aging and migration have signi cantly shaped the population composition in China, where older rural-to-urban migrant workers (age 50 and above) make up increasingly large proportions of the population [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limit studies on older rural-to-urban migrant workers in mainland China has primarily focused on their health; however, research regarding the comparison between older rural-to-urban migrant workers in mainland China and their rural and urban counterparts is scarce. To our best of knowledge, only Dan et al had specially focused on the health of older rural-to-urban migrant workers in mainland China, and their study showed that older rural-to-urban migrant workers had higher self-assessed health status, compared with older rural dwellers [ 16 ]. A growing number of comparative studies on depressive symptoms between rural-urban migrants verse urban and rural counterparts had presented a conflicting picture.…”
Section: Introductionmentioning
confidence: 99%